EP447 Clinical and ultrasound features of extra gastrointestinal stromal tumors (eGIST). (1st November 2019) - Fischerova, D; Ambrosio, M; Testa, AC; Moro, F; Franchi, D; Scifo, MC; Rams, N; Epstein, E; Alcazar, JL; Hidalgo, JJ; Van Holsbeke, C; Burgetova, A; et al.
Abstract : Introduction/Background: To describe the clinical and sonographic characteristics of extra-gastrointestinal stromal tumors (eGISTs). Methodology: This is a retrospective multicentric study. From the database of 9 large European gynecologic oncology centers we identified patients with a histological diagnosis of eGIST, who had undergone preoperative ultrasound. One author from each center reviewed stored images and ultrasound reports, and described the lesions using IOTA and MUSA nomenclatures following ultrasound evaluation form. In addition, clinical information, surgical and pathological reports were recorded. Results: Thirty-five women with eGISTs were identified, 17 incidental findings and 18 symptomatic cases. Median age was 57 years (range 21–85). Two patients (6%) had ascites and median CA 125 was 23 U/mL (range 7–403 U/mL). The vast majority of eGISTs were intraperitoneal lesions (33/35, 94%) with few retroperitoneally (2/35, 6%). The most common site was abdomen (23/35, 65.7%), and 12 lesions (34%) were in the pelvis. eGISTs were typically large (median of 79 mm) and solid tumors (31/35, 89%), the remaining eGISTs were multilocular-solid tumors (4/35, 11%). The tumor shape was mainly lobulated (20/35, 57%) or irregular (10/35, 29%). The echogenicity of solid tumors was less often uniform (8/35, 23%) but always hypoechogenic. More frequently solid tumors were non-uniform due to mixed echogenicity (13/27, 40%) or small irregular cysts (14/27, 37%). eGISTs were typically richly vascularized (color score 3 and 4, 31/35, 89%) with no shadowing (31/35, 89%). Based on pattern recognition, eGISTs were usually correctly classified as malignant lesion (32/35, 91%) and the specific diagnosis of eGIST was the most frequent among the presumed diagnosis (16/35, 46%). Conclusion: On ultrasound, eGISTs were usually solid non-uniform intraperitoneal tumors with rich vascularization and no shadowing. They may mimic ovarian fibroma or uterine fibroids but the extra-genital origin in the combination with ultrasound characteristics in experienced hands point to the diagnosis of these uncommon tumors. Disclosure: This work was supported by Charles University in Prague (UNCE 204065 and PROGRES Q28/LF1). None of the authors declare any conflict of interest.